The evolving role of maintenance therapy following autologous stem cell transplantation in multiple myeloma. Issue 10 (3rd October 2019) - Merz, Almuth Maria Anni; Merz, Maximilian; Hillengass, Jens; Holstein, Sarah A.; McCarthy, Philip
ABSTRACT: Introduction : Maintenance therapy after autologous transplantation is a standard of care in newly diagnosed myeloma. However, there is no universal answer to the question of which maintenance strategy should be pursued after ASCT? Areas covered : We conducted a MEDLINE search using the medical subject headings 'multiple myeloma', 'autologous transplantation' and 'maintenance' to identify available data from clinical trials on the role of different maintenance strategies after autologous transplantation for the newly diagnosed disease. Expert opinion : A large meta-analysis demonstrated that lenalidomide prolongs progression-free and overall survival after autologous transplantation compared to observation/placebo. Further trials confirmed that lenalidomide maintenance increases rates of high-quality responses and one study demonstrated that lenalidomide maintenance improves outcomes regardless of cytogenetic risk. Although lenalidomide can cause side effects and is associated with an increased risk of second primary malignancies, its benefits outweigh the mentioned risks. The proteasome inhibitors ixazomib and bortezomib may partially overcome the negative effects of high-risk cytogenetics. Future trials will combine different agents and monoclonal antibodies during maintenance and will investigate whether minimal residual disease status can guide maintenance duration.